ANALISIS PERBEDAAN RASIO KEUANGAN SEBAGAI TOLOK UKUR KINERJA PERUSAHAAN ASURANSI UMUM JOINT VENTURE - Dewi Pramita; Endang Kiswara (Diponegoro Journal of Accounting, 2014)
This research was aimed to distinguish between Joint Venture General Insurance Companies that have a good performance and those who are less performing well. This research is a replication of the research that has been done by Soekarno and Azhari (2009), with different variables, sample, and analyzed method. This difference occurs because of differences in rating source, this research used the rating of general insurance company from infobank magazine, while previous research was rated by AAUI (Indonesia General Insurance Association). The purpose of replication in this research was to determine whether differences in rating source will affect the differences in research results.Totally 14 samples of Joint Venture General Insurance Companies was used in this research. Data analysis method that has been used is Kruskal Wallis Test with SPSS 19 statistic program.The surveys’ results showed that there was a significant different between Joint Venture General Insurance Companies that have a good performance and those who are less performing well. There are also four ratios which are RBC, Technical Reverse to Investment Ratio, Investment to Technical Reverse and Debt on Claims Ratio, and Expense Ratio that stand as the most influential ratios to distinguish the performance of joint venture general insurance companies. In addition, the result suggest business people to be concerned toward those four ratios, to increase their companies’ performance.